Critical discourse and corpus approaches to systemic functional grammar - Hofmann, Matthias (Writer on English language); Chang, Chenguang, 1966-; Schmied, Josef J. (REAL studies, 2021)
"The present volume draws on the experience of the Workshop held in Germany in late 2018 to combine the specialisations of the two linguistic research teams of the two partner universities, Sun Yat-sen University in China and Chemnitz University of Technology in Germany. It combines more theoretical approaches by experienced scholars and case studies by young researchers on topics and texts on current Chinese developments. The contributions can also serve as a general model for open and critical international and intercultural academic discourse."--